(untitled) (Research, Society and Development, 2024)
Non-diabetic nodular glomerulosclerosis or idiopathic glomerulosclerosis is an uncommon condition with a poor prognosis. The study reports the case of a 54-year-old male patient, J.F.D.S., with no previous comorbidities, a former small-scale alcoholic, diagnosed with hypertension and asthma four months previously. During follow-up, he presented with hypertension that was difficult to control, and due to a complaint of asthenia, he underwent laboratory tests which were compatible with a progressive worsening of renal function. The renal biopsy showed non-diabetic nodular glomerulosclerosis. This case report portrays a rare disease with a poor prognosis and no established treatment, so studies are needed to better manage this condition. The objective of the study is to present and discuss a clinical case of non-diabetic nodular glomerulosclerosis secondary to multiple myeloma, describing the diagnostic methods used and the patient’s evolution.